The selection and removal of arbitrators in investor-state dispute settlement - Giorgetti, Chiara (Brill research perspectives. International investment law and arbitration., 2019)
"The Selection and Removal of Arbitrators in Investor-State Settlement examines two essential features in investor-state dispute resolution: how arbitrators are selected and removed. Both topics have received increasing scrutiny and criticism, that have in turn generated calls for reforms. In its first part, Professor Chiara Giorgetti, an expert in international arbitration, explains the selection of arbitrators procedurally and comparatively under the most-often used arbitration rules. She then reviews critically arbitrators' necessary and desirable qualities and addresses some important and related policy issues, such as diversity and repeat appointments. In her work, she also includes an assessment of the calls to review how arbitrators are appointed, and specifically the proposal by the European Commission to create a permanent tribunal to resolve international investment disputes, the UNCITRAL Working Groups III Reform Process and the rules amendment proposal undertaken by the Secretariat of the International Center for Settlement of Investment Disputes. In its second part, the monograph examines how arbitrators can be removed and reviews firs the applicable provisions, under a variety of arbitration rules, to remove arbitrators who fail to possess the necessary qualities. It then also reviews the relevant case-law on challenges. The monograph assesses appointments and removals in a multifaceted and comprehensive way, and includes a critical assessment of the reasons and calls for reform of the ISDS system"--